2019
DOI: 10.1017/aaq.2018.81
|View full text |Cite
|
Sign up to set email alerts
|

The Birch Creek Canids and Dogs as Transport Labor in the Intermountain West

Abstract: Historically, domestic dogs(Canis familiaris)have been documented as central features of Intermountain West and Great Plains Native American camps. Some of these dogs were bred specifically for largeness and stamina to haultravoisand to carry pannier-style packs. Ethnographic accounts frequently highlight the importance of dogs in moving through the Intermountain West and the plains, reporting loads as heavy as 45 kg (100 lbs). We calculated body mass from skeletal morphometric data and used these to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…A recent study of canid remains from Veratic Rockshelter by Welker and Byers (2019) focused on body size and whether these dogs had the physical traits necessary to pull travois loads and carry packs. Based on morphometric data from at least four adult domestic dogs in the Veratic Shelter faunal assemblage, Welker and Byers (2019: 101) concluded that these were robust animals capable of pulling travois loads of more than 22.6 kg (50 lbs) and carrying pack loads of at least 17.8 kg (40 lbs) as early as 3,000 years ago. If this interpretation is correct, then it seems likely that prehistoric peoples in our general study area often bred large-bodied dogs to serve primarily as pack animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of canid remains from Veratic Rockshelter by Welker and Byers (2019) focused on body size and whether these dogs had the physical traits necessary to pull travois loads and carry packs. Based on morphometric data from at least four adult domestic dogs in the Veratic Shelter faunal assemblage, Welker and Byers (2019: 101) concluded that these were robust animals capable of pulling travois loads of more than 22.6 kg (50 lbs) and carrying pack loads of at least 17.8 kg (40 lbs) as early as 3,000 years ago. If this interpretation is correct, then it seems likely that prehistoric peoples in our general study area often bred large-bodied dogs to serve primarily as pack animals.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, milling tools could have been used consistently to process plants at the study sites, but were often carried away by either the occupants or their dogs. A recent study of canid remains from Veratic Rockshelter by Welker and Byers (2019) focused on body size and whether these dogs had the physical traits necessary to pull travois loads and carry packs. Based on morphometric data from at least four adult domestic dogs in the Veratic Shelter faunal assemblage, Welker and Byers (2019: 101) concluded that these were robust animals capable of pulling travois loads of more than 22.6 kg (50 lbs) and carrying pack loads of at least 17.8 kg (40 lbs) as early as 3,000 years ago.…”
mentioning
confidence: 99%
“…This tells the reader that dog domestication was finished prior to 10,000 years ago—it was a completed process by the time clade X emerged. Finally, two papers have documented the development of relatively large dogs in parts of western North America during the Holocene, likely for their roles in transport (Welker, 2020; Welker and Byers, 2019). The emergence of these dogs is not described as an outcome of domestication, and Welker and Byers (2019: 88) state directly, “It is generally accepted that dogs were domesticated sometime before 15,000 BP in Europe and 12,500 in East Asia.” The clear inference in all of these cases is that dog domestication was a threshold crossed in the Pleistocene.…”
Section: Domesticated Dogs?mentioning
confidence: 99%
“…Second, some employ multivariate approaches based upon extensive comparative datasets to statistically identify dog and wild canid remains (Elder & Hayden, 1977; Lawrence & Bossert, 1967; Morey, 1986, 1990; Walker & Frison, 1982). Together, univariate and multivariate methods have been key elements in the development of a substantial body of knowledge concerning the origins and domestication of the dog and their dispersion around the world and their role in human cultures (Frantz et al, 2016; Horard‐Herbin, Tresset, & Vigne, 2014; Larson et al, 2012; Welker & Byers, 2019). However, both approaches are subject to drawbacks that have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%